Soilless Culture Use of Substrates for the Production of Quality Horticultural Crops - Asaduzzaman, Md (IntechOpen, 2015)
Soilless Culture - Use of Substrates for the Production of Quality Horticultural Crops provides useful information on the techniques of growing horticultural crops using either inert organic or inorganic substrates and also on use of substrates consisting locally available and inexpensive materials with adequate physical and chemical properties. The contents mainly includes influence of different substrates on horticultural crops grown under soilless culture, production of vegetables and ornamental crops in water shortage area, comparative evaluation of commercial inert substrate used for growing high value horticultural crops. In this book, interesting researches from around the world are brought together to produce a resource for teachers, researcher, and advanced students of biological science.